2015
DOI: 10.1111/jgs.13657
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Frailty After Kidney Transplantation

Abstract: OBJECTIVES To understand the natural history of frailty after an aggressive surgical intervention, kidney transplantation (KT). DESIGN Prospective cohort study (December 2008–March 2014). SETTING Baltimore, Maryland. PARTICIPANTS Kidney transplantation recipients (N = 349). MEASUREMENTS The Fried frailty score was measured at the time of KT and during routine clinical follow-up. Using a Cox proportional hazards model, factors associated with improvements in frailty score after KT were identified. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
139
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 25 publications
6
139
0
6
Order By: Relevance
“…Among recipients of a kidney transplant who met CHS criteria for frailty, nearly three-quarters were non- or intermediately frail three months post-procedure. (143) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among recipients of a kidney transplant who met CHS criteria for frailty, nearly three-quarters were non- or intermediately frail three months post-procedure. (143) …”
Section: Discussionmentioning
confidence: 99%
“…(164) While it has been suggested that “frailty” is a euphemism for patients who are terminally ill, (165) frailty may not progress in the short term and, in select cases, may be reversible. (43,143) The possibility of modifiable contributors should always be considered. Accurate information on the relative benefits and risks (including burden) of available therapies is needed for informed decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Fragility represents a measure of the physiological reserve that is related as a risk factor for adverse effects of renal transplantation, such as delayed graft function, early hospital readmission and mortality. The decline in physiological reserve promotes an increased vulnerability to stressors resulting from a deregulation of multiple physiological systems, and this may directly affect the functionality of these individuals 12,13,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a useful marker of health status and can be used to monitor response to interventions; an example of this can be seen in the study by McAdams de Marco and colleagues who explored how frailty status changed before and after kidney transplantation (34).…”
Section: Discussionmentioning
confidence: 99%
“…23,25,26,29- 33 Frailty also predicted an increased risk of falls in patients with CKD. 34,42 In the kidney transplant recipient, frailty was associated with an increased risk of early hospital readmission and delayed graft function. 35,36 Patients who were frail prior to transplantation were also more likely to have improvement in frailty after transplantation.…”
Section: Discussionmentioning
confidence: 99%